2018
DOI: 10.1016/j.jor.2018.05.046
|View full text |Cite
|
Sign up to set email alerts
|

How precisely does ultrasonographic evaluation reflect the histological status of the articular cartilage of the knee joint?

Abstract: The thickness and the grade of the articular cartilages of the knee of 34 patients who underwent total knee arthroplasty were evaluated by ultrasound (US) and by histology. The US grade correlated with the histological grade and the thickness of the articular cartilage measured by US. The thickness measured by US was significantly correlated with that measured by histology for the medial condyle. The US thickness was significantly less than the histological thickness for thicker articular cartilages. US gradin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Supporting this, Schmitz et al found that US thicknesses were positively correlated with MRI, but poor absolute agreement existed between the measurements obtained from these two imaging modalities, with US thicknesses 1.9 to 2.8 mm smaller than those on MRI [ 19 ]. On the microscopic level, the US assessment of cartilage morphology seems to correlate with the histological grade [ 20 , 21 ]. Interestingly, for the thicker cartilages, the measured thickness was significantly thinner on US than on histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this, Schmitz et al found that US thicknesses were positively correlated with MRI, but poor absolute agreement existed between the measurements obtained from these two imaging modalities, with US thicknesses 1.9 to 2.8 mm smaller than those on MRI [ 19 ]. On the microscopic level, the US assessment of cartilage morphology seems to correlate with the histological grade [ 20 , 21 ]. Interestingly, for the thicker cartilages, the measured thickness was significantly thinner on US than on histology.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, for the thicker cartilages, the measured thickness was significantly thinner on US than on histology. Maeguchi et al concluded that US grading and thickness measurements are sufficiently reliable to reflect the histological status [ 21 ]. Ultimately, we are proposing that US measures may be a relative indicator of cartilage thickness but should not be used as an absolute measure.…”
Section: Discussionmentioning
confidence: 99%
“…US has limitations such as the lack of a standardised measuring method and validated scoring system, operator‐dependent imaging and reliability and establishment of adequate acquisition parameters. On the other hand, US has major advantages over the other modalities which is highly accurate, reliable, reproducible, fast, economic and patient‐friendly method 34‐36 . Also US has lower demands for processing, lack of radiological exposure, and provides valuable practical information about the current status of the knee joint 34 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, US has major advantages over the other modalities which is highly accurate, reliable, reproducible, fast, economic and patient‐friendly method 34‐36 . Also US has lower demands for processing, lack of radiological exposure, and provides valuable practical information about the current status of the knee joint 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation